Validation of host cerebrospinal fluid protein biomarkers for early diagnosis of tuberculous meningitis in children: a replication and new biosignature discovery study. (18th August 2022) - Manyelo, Charles M.; Solomons, Regan S.; Snyders, Candice I.; Kidd, Martin; Kooblal, Yajna; Leukes, Vinzeigh N.; Claassen, Conita; Roos, Kelly; Stanley, Kim; Walzl, Gerhard; Chegou, Novel N.; ,
Abstract: Purpose: The diagnosis of tuberculous meningitis (TBM) in children is often delayed due to diagnostic difficulties. New tools are urgently needed to improve the diagnosis of the disease in this vulnerable group. The present study aimed to validate the accuracy of recently identified host cerebrospinal (CSF) biomarkers as candidates for the diagnosis of TBM in children. Materials and methods: We collected CSF samples from 87 children aged 3 months to 13 years, that were consecutively admitted at a tertiary hospital in Cape Town, South Africa, on suspicion of having TBM. We evaluated the concentrations of 67 selected host protein biomarkers using a multiplex platform. Results: Previously identified 3-marker (VEGF-A + IFN-γ + MPO) and 4-marker (IFN-γ + MPO + ICAM-1 + IL-8) signatures diagnosed TBM with AUCs of 0.89 (95% CI, 0.81–0.97) and 0.87 (95% CI, 0.79–0.95) respectively; sensitivities of 80.6% (95% CI, 62.5–92.5%) and 81.6% (95% CI, 65.7–92.3%), and specificities of 86.8% (71.9–95.6%) and 83.7% (70.4–92.7%) respectively. Furthermore, a new combination between the analytes (CC4b + CC4 + procalcitonin + CCL1) showed promise, with an AUC of 0.98 (95% CI, 0.94–1.00). Conclusions: We have shown that the accuracies of previously identified candidate CSF biomarkers for childhood TBM was reproducible. Our findings augur well for the future development of a simple bedside test for the rapid diagnosis of TBM in children.